Trinidad and Tobago : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper reviews the historical background of fuel subsidies in Trinidad and Tobago, discusses their fiscal impact and the inflationary impact of subsidy reform, summarizes the regressive distribution of subsidy benefits, focuses on the negative externalities caused by fuel subsidies and the environmental and traffic benefits of phasing them out, and discusses key factors contributing to successful reforms. Fuel subsidies in Trinidad and Tobago, established in 1974, increased dramatically owing to rising global crude oil price in the past few years and led to a growing debate on the costs and benefits of subsidy reform. Fuel subsidies have significantly contributed to the country's procyclical fiscal stance.